INCREASING SOCIAL AWARENESS AND RESPONSIBILITY THROUGH INDUSTRIAL WORK PRACTICES IN CITIZENSHIP EDUCATION - Baandaalr Lizein; Hari Mulyadi; Endang Supardi (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state. The program of vocational secondary education is industrial work practice. Industrial work practice is an integral part of education that brings students into the real world. Social awareness is a student's ability to recognize other people or awareness to foster concern which can then show the ability to empathize with other people. This research uses a qualitative approach with a retrospective case study type of research at Rina Hasanah Vocational School, Pandeglang Regency, which allows for follow-up healing or improvement of a case (treatment) after the research finds the results, so that the researcher only provides input from the research results . This research aims to describe the objective conditions of students' level of independence, learning conditions for industrial work practices in schools, implementing industrial work practices to form responsible independence as an effort to increase social awareness, and knowing the effectiveness of industrial work practices for forming independence and responsibility for vocational school students in the Regency. Pandegalang. Industrial work practices have been implemented at Rina Hasanah Vocational School. By implementing industrial work practices, it is hoped that the school can produce quality graduates who are socially sensitive and have an independent and responsible spirit. The school has provided some support for this, including holding various training and orientation programs before industrial work practices begin.